Thermostimulated Creep and Stress-Dependent Change Between Atomic Mechanism - Balerin, M. (Engineering Transactions, 1979)
It is the purpose of this paper to give an improved methodical proposal for creep experiments and an evaluation of creep and activation parameters. The interpretation of the physical processes involved and their participating atomic or more complex lattice defects are discussed.